Meningkatkan Interpersonal Skills Siswa SMP pada Mata Pelajaran Ilmu Pengetahuan Sosial Melalui Pembelajaran Kooperatif - Buana - (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2014)
This study aims at improving students’ interpersonal skills and developing learn- ing strategies with focus on the improvement of interpersonal skills. The study employs the action research design, particularly the collaborative action research.Findings of the study reveal that students’ interpersonal skills are improved through cooperative learning with re- gards to three indicators of interpersonal skils, i.e. team-work skills, communication skills and leadership skills. In addition to improvement in these skills, positive social interactions have also been developed, such as social contact and active communication amongst stu- dents. Implication of this study is development of cooperative learning in Social Science Studies to promote development of students’ interpersonal skills.